Mengeksplorasi Suara Guru di Sulawesi Selatan: Panduan Pengembangan Bahan Ajar Menulis Cerpen Berbasis Nilai Budaya Bugis - Rayhan Adi Anggara; Didin Widyartono; Kusubakti Andajani (ESTETIK : Jurnal Bahasa Indonesia, 2025)
Story writing materials grounded in Bugis cultural values. The research addresses students' difficulties in idea formulation, plot development, diction, and lack of confidence in writing short stories, compounded by limited relevant textbooks. The study aims to describe teachers' concrete needs, strategies for integrating cultural content, and to formulate guidelines for developing contextual and relevant teaching materials. Using a qualitative method with interviews involving three Indonesian language teachers in South Sulawesi, data were analyzed thematically to uncover their views and experiences. The findings highlight four key areas: (1) student difficulties in short story writing; (2) textbook limitations; (3) the potential of utilizing Bugis culture as a contextual and relevant element in teaching materials; and (4) the urgency of leveraging digital technology as a learning support tool. These findings affirm that teachers respond positively to integrating Bugis cultural values and digital technology into short story writing instruction. This integration can enrich content, strengthen student character, and make learning more relevant to students' daily lives. Thus, this research contributes to the development of contextual teaching materials that appreciate local wisdom, emphasizing the urgency of a culture-based approach in Indonesian language learning. However, this study is limited by the number of participants and requires further comprehensive material development, validation, and field testing.